2019
DOI: 10.1002/app.47608
|View full text |Cite
|
Sign up to set email alerts
|

Soft core–hard shell latex particles for mechanically strong VOC‐free polymer films

Abstract: Polymer films cast from aqueous polymer dispersions typically suffer from an inherent lack of mechanical strength when compared to their solvent-borne counterparts. This drawback can be overcome by the use nanostructured hybrid particles that contain both a hard and soft phase. In this work, we demonstrate the use latex particles consisting of a soft core with a multilobed hard shell synthesized by seeded semicontinuous emulsion polymerization with the aim of maximizing the interconnectivity of the hard phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Changing soft/hard monomer ratio may not make obvious difference in size. However, there is also work reported that the particle size was not affected by mass ratio of BA/MMA [53][54][55] in conventional emulsion-free radical polymerization. In Figure 2, we also found PDI was around 0.06 ± 0.03, except for the particle in the ratio of 1/1.…”
Section: The Influence Of Soft/hard Monomer Mass Ratio On Polyacrylatmentioning
confidence: 98%
“…Changing soft/hard monomer ratio may not make obvious difference in size. However, there is also work reported that the particle size was not affected by mass ratio of BA/MMA [53][54][55] in conventional emulsion-free radical polymerization. In Figure 2, we also found PDI was around 0.06 ± 0.03, except for the particle in the ratio of 1/1.…”
Section: The Influence Of Soft/hard Monomer Mass Ratio On Polyacrylatmentioning
confidence: 98%
“…Core–shell (CS) nanoparticles are the combination of two different phases with well‐defined properties. For instance, in the present case, it seems promising to use a hard‐core/soft‐shell system to ensure better mechanical and barrier properties in the core, protected by a soft shell responsible for forming a homogeneous, defect‐free film …”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of food packaging, better mechanical and barrier properties in the core, protected by a soft shell responsible for forming a homogeneous, defectfree film. [10][11][12][13][14][15][16] Core-shell particles are almost exclusively made using a seeded semibatch emulsion polymerization process. [17][18][19][20] Seed properties [21,22] and process control [23,24] will play a major role in determining the final morphology of the latex particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations